Acoustical impedance of a circular membrane vibrating under the influence of a force with a uniform surface distribution - RDZANEK, Witold (Archives of Acoustics, 1986)
The problem of acoustic impedance was analyzed for a circular membrane being acted on by a time-harmonic surface force with constant density. The membrane is innuersed in a lose-loss gaseous medium and the edges of the membrane are assumed to be rigid and fixed. Emploing the integral HUY-GENS-RAYLEIGH formulas the exact formulae were obtained for the acoustic pressure and power. These formulae are especially convinient for digital computer calculations in the situation where the propagation velocity of the wave on the membrane surface is much smaller than the velocity of the acoustic wave propagation through the surronnoling medium. The acoustic impedance is presented as a function of an interference parameter.